Using Talking Chips Technique to Develop the Tenth Graders' Speaking Skills at SMK PSKD 1 - Pasaribu, Daniel Sbastian (JET (Journal of English Teaching), 2017)
AbstractThe objectives of this study were to develop students’ speaking skills using Talking Chips technique and also to investigate the students’ interest in the use of Talking Chips technique inEFL class. This research was a two-cycled action research conducted in SMK PSKD 1 Jakarta. The subject of this study was the tenth graders of Accounting Class 1 consisting of 10participants from SMK 1 PSKD. The quantitative data, collected using tests, were analyzed by using independent and paired sample t-test on SPSS version 17 program. The qualitative data collected through interview, questionnaire, and observation techniques and were analyzed descriptively. The result indicated that there was significant improvement of students’ scores where the mean of students’ pre-test scores was 55.00. It increased 59.60 in post-test I and 73.40 in post-test II. Based on the result, it was concluded that through implementation of Talking Chips technique students’ speaking skills could improve. Keywords: talking chips, speaking skills, classroom action research